2018
DOI: 10.1002/pbc.27569
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hemolytic anemia and immune thrombocytopenia following hematopoietic stem cell transplant: A critical review of the literature

Abstract: Autoimmune cytopenias (AIC) post‐hematopoietic stem cell transplant (HSCT) are rare but exceptionally challenging complication. We conducted a comprehensive literature review and identified a pooled incidence of post‐HSCT autoimmune hemolytic anemia and/or immune thrombocytopenia of 2.66% (SE = 0.27) in pediatric patients. Nonmalignant disease, unrelated donor transplant, peripheral or cord blood stem cell source, conditioning regimen without total body irradiation, and presence of chronic graft‐versus‐host di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Post‐HSCT AICs are potentially life‐threatening complications and in many cases are refractory to treatment. Risk factors for developing post‐HSCT AIC include a nonmalignant disease as the indication for HSCT, an unrelated donor, and PBSC or cord blood as the graft source . These risk factors may have contributed to the development of post‐HSCT AIC in our patient.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Post‐HSCT AICs are potentially life‐threatening complications and in many cases are refractory to treatment. Risk factors for developing post‐HSCT AIC include a nonmalignant disease as the indication for HSCT, an unrelated donor, and PBSC or cord blood as the graft source . These risk factors may have contributed to the development of post‐HSCT AIC in our patient.…”
Section: Discussionmentioning
confidence: 93%
“…Autoimmune cytopenias (AIC) following allogeneic hematopoietic stem cell transplantation (HSCT) may cause significant morbidity and mortality and are often challenging to treat. 1 The incidence of AIC in children following HSCT is around 3%, and may present as autoimmune hemolytic anemia (AIHA), thrombocytopenia, red cell aplasia, neutropenia, or any combination of these phenomena. 2,3 Up to 60% of patients respond incompletely to corticosteroids or to second-line treatments such as rituximab, and in some cases remain refractory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daratumumab has been reported to be successfully used in other pediatric patients with similar complications. 9,33 Lastly, we investigated the late effects and consequences of AICdirected therapies. Short-and long-term effects of the most frequently used AIC treatments (steroids and rituximab) and supportive care measures (transfusions) are well established in various populations.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Prior studies have identified several risk factors for AIC development including nonmalignant transplant indications, chemotherapy naivety, unrelated donors, cord blood stem cell source, graft-vs-host disease (GVHD), reduced-intensity preparative regimens, serotherapy, and cytomegalovirus (CMV) reactivation. [7][8][9][10] Corticosteroids and rituximab are the most common first-line therapies for AICs. 11 However, these interventions have side effects and long-term consequences.…”
mentioning
confidence: 99%